Pengaruh Penambahan Stabilizer Alami Berbasis Umbi Lokal untuk Peningkatan Sifat Fisik dan Kimia Es Krim Buah Naga Merah (Hylocereus polyrhizus Sp.) - Rini Nofrida; Yeni Sulastri; Rucitra Widyasari; M. Abbas Zaini; Arif Nasrullah (Fakultas Teknologi Pertanian, Universitas Udayana Gedung GA, Fakultas Teknologi Pertanian, Universitas Udayana Jl. Raya Bukit Jimbaran, Jimbaran, Kuta Selatan, Bali Telp/Fax: (0361) 701801, 2018)
Ice cream is a kind of dessert with a sweet taste and served in a cold and frozen. Ice cream has a soft texture, to make the texture required stabilizer, which is one of the ingredients added in the manufacture of ice cream in order to prevent crystallization, as a binder and improve the texture. Stabilizers can be met from starch-based materials of local potency of tubers. Gelatinization of starch in the tuber flour can replace the function of the stabilizer. Some types of tubers that can be developed as an alternative source of natural stabilizer such as porang, uwi, and taro. The study is entitled